Implementing A Multi-Tiered System of Support to Increase Student Success - Hester, Peggy (East Carolina University, 2019)
West Bladen High School implemented a Multi-Tiered System of Support (MTSS) model to improve student achievement, attendance, and behavioral outcomes for students at-risk of dropping out of school. With little guidance and training, the school developed an early warning system to identify at-risk freshmen while serving retained freshmen and upperclassmen that were at risk of dropping out of school. Students were supported through the development of intervention plans and mentor support. Freshmen were further supported through Peer Group Connections (PGC), a program that developed social-emotional learning through weekly outreaches led by upperclassmen. Grades, attendance, and behavior were tracked for each student in this study. Freshmen were surveyed to determine the impact of the PGC outreaches on their outlook towards school. Finally, the FAM-S was used to determine the school’s capacity for implementation. This study revealed that teachers need more professional development to implement research-based best practices for tiered intervention and training as mentors. However, the supports offered by the school were successful in helping students reduce or eliminate risk factors for dropping out of high school.
Keywords: MTSS; Mentoring; Interventions; PBIS